A new finite difference scheme based on centroidal mean averaging for the goursat problem / Mohd Agos Salim Nasir and Ahmad Izani Md Ismail - Nasir, Mohd Agos Salim; Md Ismail, Ahmad Izani (Universiti Teknologi MARA, Pulau Pinang & and Pusat Penerbitan Universiti (UPENA), 2005)
The Goursat partial differential equation arises in the simulation and modeling of several physical problems. Several finite difference schemes have been formulated for the Goursat equation. In this paper we develop a new finite difference scheme based on centroidal mean averaging of functional values and apply the scheme to solve two Goursat problems.